Severity of adipose tissue dysfunction is associated with progression of pre-diabetes to type 2 diabetes: the Tehran Lipid and Glucose Study - Mohammad Jalali; Zahra Bahadoran; Parvin Mirmiran; Fereidoun Azizi; Farhad Hosseinpanah (BMC, 2024)
Abstract Background The association of prediabetes (Pre-DM) regression and progression with visceral adiposity index (VAI) and adipose tissue dysfunction (ATD) remains to be investigated. Methods The present cohort study was conducted within the framework of the Tehran Lipid and Glucose Study (TLGS) on 1458 Pre-DM cases (aged ≥ 21 years) who were followed for nine years. VAI was estimated based on waist circumference, body mass index, triglycerides, and high-density lipoprotein cholesterol. ATD status (i.e., absent, mild-moderate, and severe) was defined based on the age-stratified cutoff values of VAI. Multinomial logistic regression models with adjustment of potential confounders were used to estimate the chance of Pre-DM regression to normoglycemia or progression to T2D across ATD status. Results During the study follow-up, 39.0% of the participants developed T2D, and 37.7% returned to normoglycemia. Compared to mild-moderate ATD, Pre-DM subjects with severe ATD had a higher risk of developing T2D by 45% (OR = 1.45, 95% CI = 11.08-1.93). Severe ATD was also associated with a decreased chance of returning to normoglycemia by 26% (OR = 0.74, 95% CI = 0.55-0.99). Participants with severe ATD had significantly higher fasting (overall mean = 111, 95% CI = 109-112 vs. 106, 95% CI = 105-108 mg/dL) and 2h-serum glucose (overall mean = 165, 95% CI = 161-168 vs. 153, 95% CI = 149-156 mg/dL) concentrations over time. Conclusion Severe ATD was associated with an elevated risk of developing T2D and longitudinal poor-glycemic controls in Pre-DM subjects. ATD may be a simple and useful index for detecting subjects at a higher risk of Pre-DM progression to T2D, allowing for timely intervention strategies.